Prevalence And Pattern of Self-Medication Practices in Urban Area of Southern Rajasthan - Jain, Manish; Prakash, Rahul; Bapna, Dhriti; Jain, Rohit (National Journal of Community Medicine, 2015)
Background: Self-medications is widely practiced in both developed and developing countries. Inappropriate self-medication results in increases resistance of pathogens, wastage of resources, and serious health hazards. Objectives: Present study was conducted to determine the preva- lence, pattern and factors associated with self-medication among general population of an urban area of Sothern Rajasthan. Materials and Methods: A cross sectional community based study was conducted among general population in urban field practice area of Department of community medicine, RNT Medical College, Udai- pur, Rajasthan from May 2015 to August 2015. Individuals aged 18 years and above were included as study participants using Simple random method of sampling. Results: Out of total 440 study participants, 324 (73.6%) had used self-medication within last three months recall period. The practice of self-medication was more common among younger age groups, male gender and higher levels of education. Paracetamol (73.77%) and oth- er analgesics (41.98%) were most commonly used drugs. Most com- mon symptoms warranting self-medication were fever (75.31%) and headache (62.04%). Conclusion: Rising prevalence of self-medication is a matter of se- rious concern. IEC activities should be strengthened among general population to minimize the practice of self-medication.